HLA haplotypes in non-familial rheumatoid arthritis. - Legrand, L (1987)
The frequencies of HLA-A, B, C, DR, and BF haplotypes in 44 unrelated Caucasian patients with definite seropositive rheumatoid arthritis (RA) were compared with haplotype frequencies in controls. Overall, the patients had an increased risk for HLA-DR4, DR3, and DR2 antigens, but frequencies of certain DR4 or DR3 haplotypes were not increased, suggesting the importance of other HLA loci for the evaluation of risk. The presence of DR4 alone was not found to produce an increased risk for RA since the frequencies of certain DR4 haplotypes were similar in patients and controls. Increased frequencies of HLA-B18, DR4, HLA-B15, DR4, and HLA-A1, B8, Cw7, DR3 haplotypes were found in patients. RA susceptibility has been found to be associated with the last two haplotypes in some studies of multiple case families, suggesting that similar genetic mechanisms may underlie the disease in familial and sporadic forms.